CHILDREN LEARNING IN SCIENCE ON IMPROVEMENT OF LEARNING RESULTS IN SDN 1 SUDIMAMPIR - Agus Hidayat; Rian Hardiansah; Hilda Wulansari; Anggita Rahmi; Rini Sriwahyuni; Ramdan Witarsa (IKIP Siliwangi, 2018)
The purpose of this research is to improve the learning outcomes of Elementary School (ES) students through the implementation of Children Learning in Science (CLIS) in grade V SDN 1 Sudimampir Regency West Bandung (KBB). The research design was conducted using experimental research design. The study population is 60 students divided into two classes. Data collection techniques used include: tests, observations, questionnaires, and documentation. Data analysis techniques used were prerequisite analysis test consisting of: normality test, homogeneity, and final analysis using t-test. Based on the results of hypothesis test data learners learn that the value of t count of 2.941 and t table of 1.677 (t count > t table), so Ho rejected. Thus, it can be concluded that the application of CLIS proved effective against the learners' learning outcomes in science learning material changes in the properties of objects.